Choledocholithotomy without T tube Drainage: Our Initial Experience - Hoque, Md Saiful; Miah, Hasmot Ali; Bari, AKM Akramul; Nahar, Hazmoon (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Introduction: Gallstone disease occurs in 3%20% of the world population and about 15% of people with gallstone disease develop stones in the common bile duct (CBD). Smaller stones are amenable to be removed by endoscopic retrograde cholangio-pancreatography (ERCP) while larger stones require surgeryeither open or by laparoscopic. Materials and Methods: This was a prospective study between January 2010 and December 2012 in two hospitals in Chittagong, Bangladesh, on ultrasonography upper abdomen. And where ultrasonography was not able to diagnose the location and cause of obstruction than magnetic resonance cholangio-pancreatography (MRCP) was done. To rule out malignancy, contrast enhanced computerized tomography was done in selected cases. The patients were divided into two groups on the basis of managementGroup A: CBD exploration with insertion of T-tube and Group B: CBD exploration with primary closure. All operated patients underwent a longitudinal choledochotomy. Then the stones were removed and CBD was flushed with normal saline ensuring no distal obstruction. Initially we used T-tube cholangiogram to see distal clearance which was replaced by choledochoscope later on. Primary closure was done in 37 (53%) cases where T tube drainage was given in 34 (47%) cases and T-tubes were kept in situ for 910 days. Bile duct was closed with interrupted absorbable catgut 30 suture and a sub hepatic drain was kept for 48 hours. All patients were given pre-operative and post-operative antibiotics and follow up was taken for next 6 months. Results: Out of 71 patients, 46 (61%) were females and 29 (39%) males. In all patients cholecystectomy was done along with CBD exploration. Three patients who were planned for primary closure without T-tube, T-tubes were inserted due to CBD trauma, oozing, and gross swelling. Complication like biliary leakage was seen in only one patient with primary closure which was managed by keeping subhepatic drain for 5 days. Two patients in the T tube group developed wound infection while only one developed this complication in the primary closure group. No patient in the study developed cholangitis. No patient was expired in the study. Conclusions: Primary closure without external drainage after choledochotomy is feasible, safe, and cost-effective. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.38 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 41-44